Large geographic variability in the resistance of corals to thermal stress - McClanahan, Timothy R.; Maina, Joseph M.; Darling, Emily S.; Guillaume, Mireille M. M.; Muthiga, Nyawira A.; D’agata, Stephanie; Leblond, Julien; Arthur, Rohan; Jupiter, Stacy D.; Wilson, Shaun K.; Mangubhai, Sangeeta; Ussi, Ali M.; et al. (Global ecology and biogeography, 2020)
Aim Predictions for the future of coral reefs are largely based on thermal exposure and poorly account for potential geographic variation in biological sensitivity to thermal stress. Without accounting for complex sensitivity responses, simple climate exposure models and associated predictions may lead to poor estimates of future coral survival and lead to policies that fail to identify and implement the most appropriate interventions. To begin filling this gap, we evaluated a number of attributes of coral taxa and communities that are predicted to influence coral resistance to thermal stress over a large geographic range. Location Western Indo‐Pacific and Central Indo‐Pacific Ocean Realms. Major taxa studied Zooxanthellate Scleractinia – hard corals. Methods We evaluated the geographic variability of coral resistance to thermal stress as the ratio of thermal exposure and sensitivity in 12 countries during the 2016 global‐bleaching event. Thermal exposure was estimated by two metrics: (a) historical excess summer heat (cumulative thermal anomaly, CTA), and (b) a multivariate index of sea‐surface temperature (SST), light, and water flow (climate exposure, CE). Sensitivity was estimated for 226 sites using coordinated bleaching observations and underwater surveys of coral communities. We then evaluated coral resistance to thermal stress using 48 generalized linear mixed models (GLMMs) to compare the potential influences of geography, historical SST variation, coral cover and coral richness. Results Geographic faunal provinces and ecoregions were the strongest predictors of coral resistance to thermal stress, with sites in the Australian, Indonesian and Fiji‐Caroline Islands coral provinces having higher resistance to thermal stress than Africa‐India and Japan‐Vietnam provinces. Ecoregions also showed strong gradients in resistance with highest resistance to thermal stress in the western Pacific and Coral Triangle and lower resistance in the surrounding ecoregions. A more detailed evaluation of Coral Triangle and non‐Coral Triangle sites found higher resistance to thermal stress within the Coral Triangle, associated with c. 2.5 times more recent historical thermal anomalies and more centralized, warmer, and cool‐water skew SST distributions, than in non‐Coral Triangle sites. Our findings identify the importance of environmental history and geographic context in future predictions of bleaching, and identify some potential drivers of coral resistance to thermal stress. Main conclusions Simple threshold models of heat stress and coral acclimation are commonly used to predict the future of coral reefs. Here and elsewhere we show that large‐scale responses of coral communities to heat stress are geographically variable and associated with differential environmental stresses and histories.